The role of innovation clusters in Russia for investment attractiveness development and activation of foreign economic integration - CHERNYAVSKAYA, SVETLANA ALEXANDROVNA; DIKINOV, ANDZOR KHASANBIEVICH; CHERNER, NATALYA VLADIMIROVNA; ORTSKHANOVA, MARYAM ALAUDINOVNA (The journal of contemporary issues in business and government, 2021)
The actual problem of creating the most effective system of financing innovation activities at the current stage of cluster policy implementation in Russia is of particular importance and requires close attention. Foreign direct investment contributes to the activation of the investment process in the national economy, which indirectly leads to this process quality and sustainability increase. Besides, under certain conditions, foreign direct investment can contribute to the economy diversification. The competitive pressure created by foreign firms contributes to increased productivity, improved product quality, and the introduction of new management practices. It is worth noting that in times of crisis and political instability, innovation clusters are the main link of communication with foreign investors. Mainly, regional investment strategies based on the cluster approach have a positive impact on investment attraction from large investors. However, investments in individual large enterprises were not as constructive as expected. It is quite logical to assume that the consequences of the current shortage of innovation financing will be uneven. The year 2020 was quite difficult for business not only in Russia, but also around the world. Innovative business was no exception, although the development and implementation of new technologies did not stop, and in some areas even accelerated. The analysis and generalization of the specialized literature on the subject under consideration allows us to come to the conclusion that it is necessary to assess in more detail the problems of Russian cluster policy and the investment attractiveness of innovative clusters.